Augmented Reality–Assisted versus Freehand Ventriculostomy in a Head Model - Schneider, Max; Kunz, Christian; Wirtz, Christian Rainer; Mathis-Ullrich, Franziska; Pala, Andrej; Hlavac, Michal (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Ventriculostomy (VST) is a frequent neurosurgical procedure. Freehand catheter placement represents the standard current practice. However, multiple attempts are often required. We present augmented reality (AR) headset guided VST with in-house developed head models. We conducted a proof of concept study in which we tested AR-guided as well as freehand VST. Repeated AR punctures were conducted to investigate if a learning curve can be derived.Methods Five custom-made 3D-printed head models, each holding an anatomically different ventricular system, were filled with agarose gel. Eleven surgeons placed two AR-guided as well as two freehand ventricular drains per head. A subgroup of four surgeons did a total of three series of AR-guided punctures each to test for a learning curve. A Microsoft HoloLens served as the hardware platform. The marker-based tracking did not require rigid head fixation. Catheter tip position was evaluated in computed tomography scans.Results Marker-tracking, image segmentation, and holographic display worked satisfactorily. In freehand VST, a success rate of 72.7% was achieved, which was higher than under AR guidance (68.2%, difference not statistically significant). Repeated AR-guided punctures increased the success rate from 65 to 95%. We assume a steep learning curve as repeated AR-guided punctures led to an increase in successful attempts. Overall user experience showed positive feedback.Conclusions We achieved promising results that encourage the continued development and technical improvement. However, several more developmental steps have to be taken before an application in humans can be considered. In the future, AR headset–based holograms have the potential to serve as a compact navigational help inside and outside the operating room.
Keywords: augmented reality; freehand ventriculostomy; ventricular puncture; ventricular drain; holomed